Congenital Abnormalities of the Temporomandibular Joint - single conditions - Stangret, Anna; Mularczyk, Agata; Szczęśniak, Angelika; Topczewska, Katarzyna; Rogulska, Karolina (Journal of Education, Health and Sport, 2020)
Temporomandibular joint (TMJ), due to its morphological structure, is a bicondylar joint, coupled in every movement. Intensive development of TMJ occurs in the early fetal period. Diseases of the temporomandibular joints differ in etiology and symptoms. The dysfunction of temporomandibular joint may lead to many problems connected with disorders of masseter muscles and bones building this joint and tissues around it. The aim of these studies is to describe several congenital abnormalities of the temporomandibular joint. Congenital deformities of the temporomandibular joint complex can present as a growth of mandible disturbances. They can occur as single condition characterized by hyperplasia or hypoplasia of joint structures. In extreme cases it can occure as agenesis, which is lack of formation. Tempotomandibular joint may be also affected by fibrous dysplasia, form of hyperplasia. They can also occur as a complex symptom with congenital mandible deformity, what can cause the problems with correct diagnosis. Temporomandibular joint disorders constitute a significant percentage of the viscerocranium diseases. All disorders occurring within these structures are usually associated with severe pain and significant discomfort. In dental practice, it is important to know in detail the symptoms associated with diseases of temporomandibular joint and also differentiate single conditions and complex symptoms.